2018
DOI: 10.21860/medflum2018_203558
|View full text |Cite
|
Sign up to set email alerts
|

Influence of essential oil Helichrysum italicum (Roth) G. Don on the formation of non-tuberculous mycobacterial biofilm

Abstract: Sažetak. Cilj: Ispitati antimikrobni i antioksidacijski učinak te sposobnost inhibicije biofilma eteričnog ulja (EU) smilja [Helichrysum italicum (Roth) G. Don (H. italicum)] prema netuberkuloznim mikobakterijama M. avium i M. intracellulare. Materijali i metode: Za određivanje minimalne inhibicijske koncentracije (MIK) i minimalne baktericidne koncentracije (MBK) EU H. italicum prema M. avium i M. intracellulare korištena je metoda mikrodilucije u bujonu. Preživljavanje mikobakterija u Middlebrook 7H9 bujonu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Due to the extreme resistance of OPPP biofilms including those of NTM, new approaches or new substances are needed to fight biofilm formation and destruction. Our previous studies have demonstrated the great potential of EOs as inhibitors of mycobacterial adhesion or biofilm formation on polystyrene as well as inhibitors of adhesion to living cells (amoebae and HeLa cells) [27,32,33,43]. The EOs of J. communis and H. italicum from coastal regions of Croatia have been shown to be particularly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the extreme resistance of OPPP biofilms including those of NTM, new approaches or new substances are needed to fight biofilm formation and destruction. Our previous studies have demonstrated the great potential of EOs as inhibitors of mycobacterial adhesion or biofilm formation on polystyrene as well as inhibitors of adhesion to living cells (amoebae and HeLa cells) [27,32,33,43]. The EOs of J. communis and H. italicum from coastal regions of Croatia have been shown to be particularly effective.…”
Section: Discussionmentioning
confidence: 99%